EDUCATIONAL OPPORTUNITIES OF “KUTADG’U BLIG” BY YUSUF KHOS HAJIB IN THE DEVELOPMENT OF SPIRITUAL AND ETHICAL EDUCATION OF STUDENTS - Yuldasheva Malokhat Erkinovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the work of Yusuf Khos Hajib “Kutadggu blig” contains comments on the topic of educational and moral views. The work describes the educational possibilities of moral and pedagogical considerations in the moral maturity of students.